Coefficient Inequalities for Certain Subclass of Starlike Function with respect to Symmetric points related to q-exponential Function - Abbas, Zameer; Riaz, Sadia (Scientific Inquiry and Review, 2023)
The current study aims to define a class of starlike functions with respect to symmetric points subordinated with q-exponential functions. Furthermore, to investigate the coefficient inequalities and possible upper-bound of the third-order Hankel determinant for the functions belonging to our new class this study observed the new and already derived results for further analysis.